2019
DOI: 10.1111/jfpp.14177
|View full text |Cite
|
Sign up to set email alerts
|

Properties of soy protein isolate/nano‐silica films and their applications in the preservation of Flammulina velutipes

Abstract: This work evaluated the properties of soy protein isolate (SPI)/nano‐silica (nano‐SiO2) films. The particle size distribution of the film solutions and the Fourier‐transform infrared spectroscopy, X‐ray diffraction, and X‐ray photoelectron spectroscopy of films indicated that there were hydrogen bonds and coordinate bonds between the SPI and nano‐SiO2. Scanning electron microscopy images indicated that an appropriate increase in the nano‐SiO2 content improved the morphology of the films. Finally, the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 41 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…The water contact angle of the films was measured using an OCA20 (DataPhysics, Germany) contact angle instrument according to the method described by Xu et al. (2019). In brief, distilled water (10 μl) was dripped onto the film surface, and the angle between the surface and the droplet was measured.…”
Section: Methodsmentioning
confidence: 99%
“…The water contact angle of the films was measured using an OCA20 (DataPhysics, Germany) contact angle instrument according to the method described by Xu et al. (2019). In brief, distilled water (10 μl) was dripped onto the film surface, and the angle between the surface and the droplet was measured.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that nano-SiO 2 can improve the stability of a microcapsule, which was consistent with the DSC results in Section 3.4. According to reports of Xu et al [43], the addition of nano-SiO 2 to the composite film resulted in the improvement of mechanical properties because of the formation of the network structure between nano-SiO 2 and the SPI matrix. In this study, the storage stability of DMS/nano-SiO 2 was significantly (p < 0:05) higher than those of the three other groups (i.e., APESs, SMs, and DMs), which is due to the addition of nano-SiO 2 that improved the mechanical properties of the microcapsule wall materials.…”
Section: International Journal Of Polymer Sciencementioning
confidence: 98%
“…The results indicated that the addition of nano-SiO 2 had a positive protective effect on the preservation of anthocyanin microcapsules. In recent years, many studies have shown that nano-SiO 2 can improve the water resistance and mechanical properties of the composite films containing nano-SiO 2 [21,35,43,45]. The t 1/2 value of DMs/nano-SiO 2 is 253.68, 212.31, 107.98, and 90.83 d at 11%, 33%, 53%, and 75% of the relative humidity, respectively.…”
Section: International Journal Of Polymer Sciencementioning
confidence: 99%
“…Nanoparticles can be used as fillers to improve the water permeability, carbon dioxide permeability, and oxygen permeability (OP) of the film for enhancing the physical properties of packaging materials. 15 Nanoparticles such as nano-silver, 16 nano-clay, 17 carbon nanoparticles, 18 and silicon dioxide, [19][20][21] ZnO nanoparticles, 22 exhibit improved mechanical, protective, and thermal properties in food packaging materials. Silica nanoparticles (nano-SiO 2 ) can effectively improve the properties of materials because of high surface energy, large surface atom ratio, large specific surface area, and its small particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Silica nanoparticles (nano-SiO 2 ) can effectively improve the properties of materials because of high surface energy, large surface atom ratio, large specific surface area, and its small particle size. 15,20 Han and Wang 20 reported that the incorporation of SiO 2 nanoparticles can improve the water barrier and mechanical properties of SPI films. Xu et al 15 reported that a SPI with nano-SiO 2 can prolong the shelf life and improve the production of flammulina velutipes.…”
Section: Introductionmentioning
confidence: 99%